The Biopolitics of the Body with Disabilities: How Dual Stigma Controls Accessibility and Shapes the Subjectivity of Persons with Disabilities in Public Spaces - Hariashari Rahim; Putu Wijangga; Risma Risma (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
Background: Urban public spaces are essential for the social participation of persons with disabilities. However, accessibility is often hampered, not just a matter of facilities, but of the biopolitical forces that construct "disability" and control the body and subjectivity. This research aims to explain why accessibility is still limited despite inclusive policies. Methods: A systematic review of 28 scientific articles was conducted. The study selection process involves rigorous screening (inclusion/exclusion) after a comprehensive search. Data were extracted and categorized into three main themes namely biopolitics and disability body control, multiple stigma and intersectional discrimination, and accessibility and public space. Manuscripts are dominated by qualitative studies and literature reviews, with most of the publications current (2021-2025). Results: Multidimensional discrimination was identified, including social exclusion, barriers to access to services, structural/policy discrimination, and bullying. Stigma (external and internal) is the root of the problem, affecting autonomy and quality of life. Biopolitical control manifests itself in the institutional's determination of norm-based access and the system's slow response to the needs of people with disabilities. Conclusion: The limitations of accessibility, despite the existence of policies, are caused by policy failures to dismantle deep stigmas, structural discrimination, and biopolitical controls. Existing policies tend to only touch the surface, do not change the construction of "flaws" or empower subjectivity fundamentally. A comprehensive approach that addresses biopolitical barriers and stigma is absolutely necessary to achieve true inclusion.